Miradas sobre las prácticas reflexivas en la formación de maestras y maestros - Giraldo García, Luz Karime (Universidad Santiago de Cali, 2017)
In this article we looked at reflexive practices in teacher training, taking into account the experiences as a teacher of practice, as well as the implications in the teaching task of the students of the Bachelor 's in the faculties of education. Reflective practices are recognized as a professional competence to strengthen the quality of education relevant to their development in contexts of profes-sional practice.The ideas and reflections were raised due to the current term of reflexive prac-tice in the processes of teaching and learning, classroom research and teacher training. It is articulated with teachers' thinking and is used as a methodology for teachers to reflect on their own practice and that of their fellow students. It has also been established as a competition closely related to innovative conti-nuing teacher training programs